2015
DOI: 10.1021/ma502410d
|View full text |Cite
|
Sign up to set email alerts
|

Semiconducting Nanotubes by Intrachain Folding Following Macroscopic Assembly of a Naphthalene–Diimide (NDI) Appended Polyurethane

Abstract: This article describes a well-designed supramolecular assembly of a classical polyurethane scaffold containing pendant n-type semiconducting naphthalene− diimide (NDI) chromophores and consequences on excited state dynamics and charge carrier mobilities. A polycondensation reaction between hexamethylene−diisocyanate and a NDI-containing diol in the presence of a chiral "monofunctional impurity" produced the desired polymer (P1) with a predictable degree of polymerization and end-capping by chiral units. In ali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 105 publications
3
44
2
Order By: Relevance
“…However, FE‐SEM micrographs of the same solution also displayed the presence of large multimolecular composites from spherical to cubical to rod‐like nanostructures (Figure B and Figure S13A, Supporting Information) . Formation of such large composite structures can be engendered due to the multistep aggregation process which involve aggregation, fusion, and then smoothing of the surface of aggregates, and are reported in the literatures (Figure S13B, Supporting Information) . We believe that the existence of above multistep aggregation phenomenon can be attributed to the unfavorable hydrophobic/hydrophilic ratio as well as to the involved secondary interactions induced by amide bonds of each peptidic repeat units and by few of the unfunctionalized free amino groups at pendants terminal.…”
Section: Resultssupporting
confidence: 66%
“…However, FE‐SEM micrographs of the same solution also displayed the presence of large multimolecular composites from spherical to cubical to rod‐like nanostructures (Figure B and Figure S13A, Supporting Information) . Formation of such large composite structures can be engendered due to the multistep aggregation process which involve aggregation, fusion, and then smoothing of the surface of aggregates, and are reported in the literatures (Figure S13B, Supporting Information) . We believe that the existence of above multistep aggregation phenomenon can be attributed to the unfavorable hydrophobic/hydrophilic ratio as well as to the involved secondary interactions induced by amide bonds of each peptidic repeat units and by few of the unfunctionalized free amino groups at pendants terminal.…”
Section: Resultssupporting
confidence: 66%
“…( R )‐NDI showed a much larger maximum conductivity ( φ ∑ μ ) max of 1.7×10 −5 cm 2 V −1 s −1 and a long carrier lifetime, in which φ and ∑ μ represent photocarrier generation efficiency and the sum of hole/electron mobilities. The observed maximum conductivity value is slightly smaller than those of the previously studied NDI systems by the same method (3.5×10 and 3.3×10 −5 cm 2 V −1 s −1[27] ) but within a comparable range. The contrast of ( φ ∑ μ ) max between ( R )‐NDI and NDI‐2 suggested that the periodic assembly supported by H‐bonding and π–π interaction was indeed important for providing effective charge‐transport pathways.…”
Section: Resultscontrasting
confidence: 55%
“…Eur.J. 2018, 24,1938 -1946 www.chemeurj.org previously studied NDI systemsb yt he same method (3.5 10 [26] and 3.3 10 À5 cm 2 V À1 s À1 [27] )b ut within ac omparable range. The contrasto f( fAEm) max between (R)-NDIa nd NDI-2 suggested that the periodic assembly supported by H-bonding and p-p interaction was indeed important for providing effective charge-transport pathways.T he TRMC profile of (S)-NDI was also recorded similarly and yieldedt he (fAEm) max of 1.4 10 À5 cm 2 V À1 s À1 that was essentially comparable with the value of (R)-NDI ( Figure S12, Supporting Information).…”
Section: Charge-carrier Transporting Propertiesmentioning
confidence: 90%
“…By combining the above ϕ value and ϕ Σ μ , the electron mobility of Fc‐NDI‐Fc is, at a minimum, 1.4×10 −3 cm 2 V −1 s −1 . This electron mobility is comparable with other NDI π‐systems determined by FP‐TRMC measurements that were carried out under air . The electron mobility was lower in case of bulk Fc‐NDI‐Fc samples (Figure S6, Supporting Information), indicating that the segregated‐stack structure in the crystal facilitated the electron‐transport event through the NDI conduits.…”
Section: Methodsmentioning
confidence: 99%